The Influence of job satisfaction on turnover intentions within the Sarawak’s hotel industry / Latif Amit and Walter Anyie Tomy - Amit, Latif; Tomy, Walter Anyie (2008)
In Malaysia, issue of turnover is not a new issue where people still have a conservative mindset in choosing job and leaving their job and it is believed that, this issue exists in almost all firm or organization in Malaysia. This issue is unavoidable due to culture, norms and environmental, includes inside and outside, of one organization. The two objectives of this study are: first, to examine the relationships between job satisfaction components (intrinsic and extrinsic) and turnover intentions, and second, to examine which element of job satisfaction affect the most. Statistical analyses on a sample of 105 hotel employees working on the Kuching’s city, Sarawak, Malaysia revealed that the extrinsic satisfaction had an important impact on turnover intention whereas intrinsic satisfaction had a relationship with one’s intention to leave. Implications for managerial practices and future research are discussed.